Structure-based Virtual Screening and Hit Identification of Novel designed Quinazolin-4(3H)-one Derivatives as Antitubercular Agent against Targets Polyketide Synthase 13 and DNA gyrase of Mycobacterium tuberculosis - Gnanavelou, Revathi; Perinbaraj, Sowmiya; Girija, Konda Reddy (Current Drug Discovery Technologies, 2025)
Introduction After COVID-19, tuberculosis remained the world's second most infectious fatal disease in 2022, with about 410 million people developing MDR TB, according to WHO. The fast increase of MDR and XDR-TB has posed a significant clinical problem in tuberculosis treatment. Bedaquiline, the first FDA-approved medicine for MDR-TB treatment, has caused cardiotoxicity and hepatotoxicity due to high lipophilicity or hERG potassium channel blockage throughout the last four decades. To overcome medication resistance and toxicity, there is an urgent need to create innovative drugs with improved efficacy against specific enzymes. Methods The work focused on the biological importance of the Quinazoline pharmacophore scaffold, and it involved the virtual screening and development of 180 novel Quinazoline derivatives in order to find potential hit candidates against molecular dual targets (Pks-13 esterase and DNA gyrase). Based on docking scores lower than (-7.5, -7.6 kcal/mol) of the standard compound, 80 drug molecules were screened using AUTODOCK Vina and filtered by ADMET profile. The top five HIT compounds developed with good binding interactions, acceptable ADME features that obeys the Lipinski Rule of Five, and no toxicity produced as compared to standard bedaquiline were chosen. Results and Discussion Docking scores showed that compound RBSI64 had a substantial binding affinity against dual targets (-11.6, -8.2 kcal/mol) than Bedaquiline (-7.5, -7.6 kcal/mol). MD simulation at 100 ns was carried out to investigate the protein's dynamic behaviour with the standard and ligand complex. Conclusion The results indicated that RBSI64 could be a useful template for developing MDR and XDR-TB inhibitors. The current study contributes to the identification of promising antitubercular candidates against targeted enzymes.
Keywords: virtual screening